The Role and Development of Nasyiatul Aisyiyah in Medan City - Rahmawati, Rena Sri; Siregar, Yusra Dewi; Ritonga, Sakti (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This study examines the development and initiatives of Nasyiatul Aisyiyah in Medan City from 2016 to 2023, highlighting its significant role in the region's social and religious dynamics. Employing historical research methods, including heuristics, verification, interpretation, and historiography, data were collected through observations, interviews, and documentation at the Muhammadiyah Regional Leadership (PDM) office. Findings reveal significant progress in Nasyiatul Aisyiyah's activities, with regular events despite challenges during the Covid-19 pandemic, which led to temporary disruptions. Nonetheless, the organization remained active in disaster relief efforts, fundraising, and mask distribution. Plans for 2022-2023 include resuming programs and introducing new initiatives such as parenting classes, disaster response, leadership training, international symposiums, PASHMINA, and TOT entrepreneurship. The study explores the contributions and growth trajectory of Nasyiatul Aisyiyah in fostering community welfare and religious education, employing qualitative methodologies, including interviews and organizational document analysis. The research identifies challenges such as resource limitations and sociopolitical constraints but highlights the organization's adaptive strategies and community-centric approach in overcoming obstacles and advancing its mission. This research contributes to a deeper understanding of the role of women’s organizations in regional development and offers insights into the potential for similar initiatives in other contexts.